2022
DOI: 10.3390/jof8070682
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Fungicidal Activities of N-Chlorotaurine and Conventional Antiseptics against Candida spp. Isolated from Vulvovaginal Candidiasis

Abstract: N-chlorotaurine (NCT), the N-chloro derivative of the amino acid taurine, is a long-lived oxidant produced by stimulated human leucocytes. NCT has antimicrobial activities which are generally enhanced in the presence of organic material. The aim of this study was to investigate fungicidal effects of NCT and conventional antiseptics against Candida isolated from vulvovaginal candidiasis (VVC). Chlorhexidine (CHX, 1.6%), octenidine dihydrochloride (OCT, 0.08%), povidone iodine (PVP-I, 8%), boric acid (8%), and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…Compared to quaternary ammonium compounds, OCT exhibits reduced toxicity due to the absence of amide and ester constituents within its chemical composition [29]. Previous studies have reported that OCT demonstrates antifungal and antibiofilm properties [30][31][32][33][34][35]. The current study reveals that OCT effectively inhibits the growth of hyphae in C. albicans, preventing biofilm formation and disrupting mature biofilms.…”
Section: Discussionmentioning
confidence: 56%
“…Compared to quaternary ammonium compounds, OCT exhibits reduced toxicity due to the absence of amide and ester constituents within its chemical composition [29]. Previous studies have reported that OCT demonstrates antifungal and antibiofilm properties [30][31][32][33][34][35]. The current study reveals that OCT effectively inhibits the growth of hyphae in C. albicans, preventing biofilm formation and disrupting mature biofilms.…”
Section: Discussionmentioning
confidence: 56%
“…However, povidone iodine is less-irritant, favoring its use. Hacioglu et al [21] tested the efficacy of different antiseptics compounds as a potential anti-fungal for isolates of VVC and reported that N-Chlorotaurine was the most effective agent followed by octenidine dihydrochloride and povidone iodine. They advocated the use of N-Chlorotaurine.…”
Section: Candida Glabrata and Candida Krusei]mentioning
confidence: 99%